Age and Origin of the Founder Antithrombin Budapest 3 (p.Leu131Phe) Mutation; Its High Prevalence in the Roma Population and Its Association With Cardiovascular Diseases - Bereczky, Zsuzsanna; Gindele, Réka; Fiatal, Szilvia; Speker, Marianna; Miklós, Tünde; Balogh, László; Mezei, Zoltán; Szabó, Zsuzsanna; Ádány, Róza (Frontiers in Cardiovascular Medicine, 2021)
Background: Antithrombin (AT) is one of the most important regulator of hemostasis. AT Budapest 3 (ATBp3) is a prevalent type II heparin-binding site (IIHBS) deficiency due to founder effect. Thrombosis is a complex disease including arterial (ATE) and venous thrombotic events (VTE) and the Roma population, the largest ethnic minority in Europe has increased susceptibility to these diseases partly due to their unfavorable genetic load. We aimed to calculate the age and origin of ATBp3 and to explore whether the frequency of it is higher in the Roma population as compared with the general population from the corresponding geographical area. We investigated the association of ATBp3 with thrombotic events in well-defined patients' populations in order to refine the recommendation when testing for ATBp3 is useful. Methods and Results: Prevalence of ATBp3, investigated in large samples (n = 1,000 and 1,185 for general Hungarian and Roma populations, respectively) was considerably high, almost 3%, among Roma and the founder effect was confirmed in their samples, while it was absent in the Hungarian general population. Age of ATBp3—as calculated by analysis of 8 short tandem repeat sequences surrounding SERPINC1—was dated back to XVII Century, when Roma migration in Central and Eastern Europe occurred. In our IIHBS cohort (n = 230), VTE was registered in almost all ATBp3 homozygotes (93%) and in 44% of heterozygotes. ATE occurred with lower frequency in ATBp3 (around 6%); it was rather associated with AT Basel (44%). All patients with ATE were young at the time of diagnosis. Upon investigating consecutive young (<40 years) patients with ATE (n = 92) and VTE (n = 110), the presence of ATBp3 was remarkable. Conclusions: ATBp3, a 400-year-old founder mutation is prevalent in Roma population and its Roma origin can reasonably be assumed. By the demonstration of the presence of ATBp3 in ATE patients, we draw the attention to consider type IIHBS AT deficiency in the background of not only VTE but also ATE, especially in selected populations as young patients without advanced atherosclerosis. We recommend including the investigation of ATBp3 as part of thrombosis risk assessment and stratification in Roma individuals.